Islam is not a "religion"-global religious history and early twentieth-century debates in British Malaya - Maltese, Giovanni (Method and Theory in the Study of Religion, 2021)
Lately, Islamicists have called to discard "religion" as a conceptual tool and/or to use the "Qur.anic term" din instead, arguing that "religion" entails Eurocentric bias. Analyzing how Fazl-ur-Rahman Ansari conceptualized Islam and religion in the late 1930s and early 1940s, this article presents a threefold argument. Firstly, I argue that a global history approach which examines in a poststructuralist framework how "Islam" and "religion" are used in concrete contexts is better suited to address the problem of Eurocentrism in both Religious Studies and Islamic Studies. Secondly, I challenge the scholarly thesis that twentieth-century Southeast Asian intellectual debates which referred to Islam as religion were mere emulators of debates conducted in the "West." Instead of assuming isolated histories and ignoring Southeast Asian debates, I contend that the current use of and debates about conceptualizations of Islam as/and religion are the product of one and the same discourse-a result of global negotiation processes in which Europeans were as involved as Southeast Asia-based non-Europeans, even if they did not speak from the same position of power. Finally, I submit that the approach of global religious history opens new perspectives on contemporary Malaysian politics.
CRIS-Team Scopus Importer:2024-03-27
Keywords: British Malaya; Eurocentrism; Fazl-ur-Rahman Ansari; Islam; Malaysia; Shahab Ahmad